Optimalisasi Pelayanan Tabungan Haji Berbasis Aplikasi Digital Pada Bank Syariah Indonesia Kcp Surabaya Manukan - Hidayah, Rachmania Noor; Marseto, Marseto (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Digital transformation in Islamic banking is a key strategy for delivering efficient, fast, and relevant services to modern society. One service significantly impacted is the Hajj savings product, which can now be accessed through digital platforms such as Bank Syariah Indonesia's (BSI) Byond Mobile app. This community service activity aimed to evaluate the optimization of digital-based Hajj savings services at BSI's Surabaya Manukan branch. The method used was a descriptive qualitative approach, with data collected through field observations, informal interviews with bank staff, and documentation of service activities. The results of the community service program showed that the use of the Byond Mobile application accelerated the account opening process, reduced administrative errors, and increased customer convenience and trust. Furthermore, the involvement of student interns supported digital literacy among customers unfamiliar with technology. This program not only benefited the community but also provided students with practical experience and a meaningful role in improving Sharia-compliant public services. The findings of the activity recommended strengthening digital literacy and technical training to enhance the effectiveness of similar services in the future.